IMPLEMENTASI REWARD DAN PUNISHMENT DALAM MENINGKATKAN KEDISIPLINAN BELAJAR SISWA DI MTS ROUDLOTUL MUTA’ALIMIN MOROPELANG BABAT LAMONGAN - Ahmad Suyuthi; Achmad Sun'an (Universitas Islam Lamongan, 2018)
A thesis this is the result field research on the implementation of reword and punishment in an attempt to improve a key insight about learning discipline of to their students in an institution , loan institution program program lembaga kur was a continuation of undang-undang no 14 years 2005 on teachers and lecturers article 1 verse 1 about the role of teachers needed in sow and and discipline of has encouraged the growth of to their students , a professional teacher of with the main task of educate , for the allocation of teaching , from before them and behind , task will be to steer , take over as coach of , felt on the whole , and evaluate school tuition to early age education usia dini early childhood education an education channel formal , access to primary education , and education medium enterprises and the status of those things islamic junior high school MTs Roudlotul Muta‘allimin Moropelang based on Ahlussunnah Wal-Jama’ah .In an attempt to improve discipline of students to study at their own locations those things RoudlotulMuta’aliimin Moropelang now applied Reword and punishment to increase of the quality of learning the primary school students .A thesis which assumed the title of “the implantation of the Rewards and Punishment in improving the discipline of students to study at their own locations those things roudlotul Muta’allimin Moropelang Babat.